Impact of occupational exposure on job satisfaction and overall happiness among Chinese physicians and nurses: A cross‐sectional study. (23rd May 2022) - Shi, Lei; Zhang, Jinchan; Xiao, Shujuan; Lin, Huang; Zhao, Chongbang; Zhao, Shihong; Ou, Weiyan; Li, Hailin; Zhang, Chichen
Abstract: Aims: This study aims to investigate the impact of occupational exposure on job satisfaction and overall happiness and to identify related factors of job satisfaction and overall happiness among physicians and nurses. Background: Occupational exposure against physicians and nurses has become one of the most serious public health issues worldwide. Methods: A cross‐sectional study was conducted among physicians and nurses from 14 public tertiary hospitals using purposive sampling. Propensity score matching was used to compare job satisfaction and overall happiness among physicians and nurses with and without occupational exposure. Furthermore, binary logistic regression analysis was used to identify and analyse the influencing factors of job satisfaction and overall happiness. Results: A total of 2139 physicians and nurses (55.59%) from 3791 participants had experienced occupational exposure hazards. Before matching, the job satisfaction and overall happiness among the physicians and nurses were 38.54% and 42.14%, respectively. Participants who experienced occupational exposure were more likely to develop job dissatisfaction (OR = 1.08, 95% confidence interval [CI]: 0.90–1.28) and overall unhappiness (OR = 1.24, 95% CI: 1.05–1.46) than those who did not. Participants' work experience, self‐evaluated health status, satisfaction with the work environment, evaluation of doctor–patient relationship and stress were common factors affecting job satisfaction and overall happiness. Conclusions: Our findings suggest that physicians and nurses who experience occupational exposure are more likely to develop job dissatisfaction and overall unhappiness, especially if they have shorter work experience and a tense or neutral relationship with patients. Implications for Nursing Management: It is necessary to pay attention to the occupational exposure. When physicians and nurses experience occupational exposure, managers could provide support to prevent job dissatisfaction and unhappiness.